2004
DOI: 10.1016/j.pain.2004.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Distraction modulates connectivity of the cingulo-frontal cortex and the midbrain during pain—an fMRI analysis

Abstract: Neuroimaging studies with positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) have delineated a human pain network in vivo. Despite the recognition of cerebral structures engaged in pain transmission, the cerebral mechanisms involved in pain modulation are still not well understood. Here, we investigated healthy volunteers using fMRI during experimental heat pain and distraction induced by a visual incongruent color-word Stroop task. A factorial design permitted categorical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
312
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 615 publications
(339 citation statements)
references
References 52 publications
22
312
0
5
Order By: Relevance
“…In contrast, the ventrolateral column receives convergent input from both the superficial and deep dorsal horn relaying nociceptive afferent information from visceral, muscle, and C-fiber skin nociceptors as well as visceral inputs from the nucleus of the NTS and sacral spinal cord. Functional neuroimaging studies in humans indicate that PAG activation by nociceptive inputs is modulated by attention, emotion, expectation of pain and expectation-related placebo analgesia [54][55][56][57][58][59][60][61]. Experimental studies using chemical microstimulation indicate that the different columns of the PAG organize different coping strategies to pain and other stressors [62][63][64][65][66].…”
Section: Descending Pain Modulatory Systemmentioning
confidence: 99%
“…In contrast, the ventrolateral column receives convergent input from both the superficial and deep dorsal horn relaying nociceptive afferent information from visceral, muscle, and C-fiber skin nociceptors as well as visceral inputs from the nucleus of the NTS and sacral spinal cord. Functional neuroimaging studies in humans indicate that PAG activation by nociceptive inputs is modulated by attention, emotion, expectation of pain and expectation-related placebo analgesia [54][55][56][57][58][59][60][61]. Experimental studies using chemical microstimulation indicate that the different columns of the PAG organize different coping strategies to pain and other stressors [62][63][64][65][66].…”
Section: Descending Pain Modulatory Systemmentioning
confidence: 99%
“…Most often studies found a reduction in pain experience (McCaul and Malott 1984;Miron et al 1989;Petrovic et al 2000;Tracey et al 2002;Valet et al 2004;Van Damme et al 2008; but see Goubert et al 2004;McCaul et al, 1992). Directing attention away from pain also dampens the processing of nociceptive input in various brain structures (Bantinck et al 2002;Valet et al 2004;Villemure and Bushnell 2009), in particular through the activation of prefrontal areas (Bantinck et al 2002;Petrovic et al 2000;Valet et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have argued that distraction is effective because attention is directed towards a stimulus from another perceptual modality (McCaul and Malott, 1984;Miron et al 1989;Petrovic et al 2000;Tracey et al 2002;Valet et al 2004). This hypothesis however is premature since distraction tasks used in previous studies involved both (1) directing attention towards a perceptual modality other than nociception and (2) directing attention towards a spatial location other than the location of the painful stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Il a été montré par la suite en TEP que les aires préfrontales et pariétales étaient impliquées dans des processus attentionnels [3,4] qui sont contemporains de toute stimulation douloureuse (on tourne naturellement son attention vers la zone douloureuse). Ces données ont, depuis lors, été répliquées par d'autres équipes de recherche, utilisant les techniques TEP et IRMf [5,6] ( Figure 1C). Il faut toutefois noter que même si ces aires ne sont pas spécifiques, le contexte attentionnel peut influencer directement les aires de la nociception, et que la perturbation des aires attentionnelles détermine le degré d'attention accordé à la stimulation nociceptive [7].…”
Section: La Physiologie De La Douleur Ou Nociceptionunclassified
“…De nombreuses études utilisant l'imagerie cérébrale ont testé les effets antalgiques, et en parallèle les effets sur l'activité cérébrale, d'un certain nombre de situations antalgiques. Ainsi, des situations physiologiques comme la diversion [6,41], l'hypnose [42], mais aussi des effets pharmacologiques, comme l'effet des opiacés [43,44] ou l'effet placebo [42,45] créent, de manière surprenante, des activités qui convergent dans une zone cérébrale du cortex frontal médian, le cingulaire rostral, et dans le cortex orbitofrontal. Il est admis que ces structures puissent être à l'origine de contrôles inhibiteurs descendants sur la SGPA et que cette région puisse être impliquée dans des mécanismes antalgiques physiologiques, au sens large [46].…”
Section: Imagerie Cérébrale Appliquée à L'étude Des Mécanismes Analgéunclassified